Genotyping of carbapenem resistant Acinetobacter baumannii isolated from Egyptian patients - Heba Ahmed Mohamed; Gamal Fadl Mahmoud Gad; Mona Fattouh Mohamed; Hend Harby Ahmed; Ameer Effat Elfarash; Nahed Fathallah Fahmy (Novel Research in Microbiology Journal)
Acinetobacter baumannii has recently been known as a major cause of hospital- and community-acquired infections. Carbapenem resistant A. baumanni (CRAB) has been recorded to be resistant to nearly all antibiotics, including the last resort antibiotics; carbapenems. This study aimed to detect the carbapenem resistance levels and mechanisms, in addition to the genotyping of A. baumanni in Upper Egypt. About 200 clinical samples were collected from different wards of Sohag University Hospital, Egypt, from which 20 A. baumannii isolates were recovered and then identified using conventional methods and Polymerase Chain Reaction (PCR). Antibiotic sensitivity testing was carried out using the Disk diffusion method, followed by PCR testing of the common carbapenemase-encoding genes, including OXA-51, OXA-58, KPC, GES, IMP, NDM, VIM, SIM, and GIM. Genotyping was performed using the Enterobacterial Repetitive Intergenic Consensus-Polymerase chain reaction (ERIC-PCR). About 85 % of A. baumannii strains were multidrug resistant (MDR), and high rate of Extreme drug resistant (XDR) A. baumannii (70 %) was detected. Carbapenem resistance was detected in 65 % of A. baumannii isolates, 70.58 % of MDR isolates, and 85.7 % of XDR isolates, respectively. Carbapenemase- encoding genes, including blaOXA-51, VIM, NDM, and GES, were detected in 100 %, 100 %, 76.9 2 % and 76.92 % of the carbapenem resistant A. baumannii (CRAB) isolates, respectively. The blaIMP and blaKPC genes had lower prevalence rates of 15.38 % and 30.77 %; respectively, whereas the SIM, GIM, and OXA-58 genes were not detected in any of the tested A. baumanni isolates. All of the MDR isolates carried three or more the carbapenemases encoding genes, and 85.7 % of the XDR isolates carried four or more of the carbapenemase-encoding genes. The dendrogram constructed from the ERIC-PCR results showed that the A. baumannii isolates were divided into three different clusters.